Diary of a wimpy kid : Greg Heffley's journal - Kinney, Jeff. (New York : Amulet Books, 2007)
Greg records his sixth grade experiences in a middle school where he and his best friend, Rowley, undersized weaklings amid boys who need to shave twice daily, hope just to survive, but when Rowley grows more popular, Greg must take drastic measures to save their friendship.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
Book Links-starred, January 2008.
Booklist, April 2007.
Bulletin (Center for Children's books), June 2007.
Keywords: Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Diaries -- Fiction; Friendship -- Fiction; Humorous stories; Middle schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Friendship -- Fiction; Humorous fiction; Middle schools -- Fiction; School stories; Diary fiction; Humorous fiction